Evolution of lateral tectonophysical stresses in the spherical shell convection with an immobile supercontinent - Baranov, A.; Bobrov, A.; Tenzer, R.; Chuvaev, A. (Frontiers in Earth Science, 2025)
We investigate the evolution of horizontal stress field after implementing a supercontinent into spherical mantle model with phase transitions, the temperature- and pressure-dependent rheology, while assuming that the mantle is heated from the base and from within. Before implementation of the supercontinent, the overlithostatic horizontal stresses in the areas of mantle upwellings/downwellings are about ±25 MPa and more, whereas for the rest upper mantle horizontal stresses are in the range of ±15 MPa. The supercontinent covered one-third of the Earth`s surface and it is modeled as an undeformable, highly viscous immobile lid with respect to the ambient mantle and it is abruptly imposed on well-developed mantle convection. The area of supercontinent is limited by a spherical angle (θ ≤ 66.4◦). After implementation, the mantle flow is rearranged and a group of upwelling mantle flows is formed under the supercontinent and their hot heads increase in size due to the heat-insulating effect of the supercontinent, while quasi-linear subduction zones increase in the oceanic regions. As a result, the average temperature of the area under the supercontinent rises over time and becomes higher than the average temperature of the suboceanic area, where cold descending mantle flows intensify. Аt the depth covering the interval from 300 to 400 km under the supercontinent the temperature rises on average by 60 K. Formed under the supercontinent, upwelling mantle flows dramatically change the stress pattern in the supercontinental area producing tensional stresses in the supercontinent and overlithostatic compressive horizontal stresses in the subcontinent mantle. Tensile overlithostatic horizontal stresses inside the supercontinent change from 25 to 50 MPa in different continental areas, whereas beneath the supercontinent the overlithostatic compressive horizontal stresses in the subcontinent mantle are about 20–60 МPа. Only for the model with weak zone around the supercontinent stresses can reach 100 MPa.